Assessing the impact of climate change on the water balance in semi-arid West Africa: a SWAT application - Verbeeten, E.; Barendregt, A. (IfGIprints, 2007)
This paper discusses the application of the Soil and Water Assessment Tool (SWAT) in the evaluation of the impacts of climate change on hydrological services provided by dry forests and savannah ecosystems in Burkina Faso, West Africa. Preliminary results demonstrate that erratic and intensive rainfall leads to higher peaks of discharge in the rainy season. This results in a decline of water availability and less groundwater recharge. Under such climatic conditions the sediment load also increases, affecting the water quality. Although general trends are clear, the quantitative impact of climate change yet has to be established. An evaluation of uncertainty and sensitivity of input parameters is now undertaken. Then the most sensitive and uncertain input datasets will be revised to improve the accuracy of predicted outputs. However, the first results are promising. SWAT seems to be an appropriate tool for evaluation of climate change impacts on the water balance.